A prospective, multicenter evaluation of point‐of‐care ultrasound for appendicitis in the emergency department. (14th September 2021) - Becker, Brent A.; Kaminstein, Daniel; Secko, Michael; Collin, Mark; Kehrl, Thompson; Reardon, Lindsay; Stahlman, Barbara A.
Abstract: Objective: The main objective of this study was to evaluate the accuracy of point‐of‐care ultrasound (POCUS) for the diagnosis of appendicitis in a general emergency department (ED) population as performed by emergency physicians with variable ultrasound experience. Methods: We performed a prospective, multicenter, observational study examining a convenience sample of adult patients with potential appendicitis presenting to the ED between July 2014 and February 2020. Each emergency physician–performed POCUS was interpreted at the bedside and retrospectively by an expert reviewer. Test characteristics were calculated for POCUS and blinded expert interpretation compared to surgical pathology in patients undergoing appendectomy and advanced imaging in patients managed nonoperatively. Results: A total of 256 subjects were included in the primary analysis with an overall appendicitis prevalence of 28.1%. For the diagnosis of appendicitis, POCUS demonstrated an overall sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio of 0.85 (95% confidence interval [CI] = 0.74 to 0.92), 0.63 (95% CI = 0.56 to 0.70), 2.29 (95% CI = 1.85 to 2.84), and 0.24 (95% CI = 0.14 to 0.42), respectively. Expert review yielded a lower sensitivity (0.74 [95% CI = 0.62 to 0.83]) with a similar specificity (0.63 [95% CI = 0.56 to 0.70]). Conclusion: POCUS is moderately accurate for acute appendicitis as performed by emergency physicians with a wide range of ultrasound expertise, but lacks adequate sensitivity and specificity to function as a definitive test in an undifferentiated ED population. Further study is warranted to elucidate the optimal role of integrated POCUS in the general approach to suspected appendicitis.